PROCESSING CORN COB WASTE AS AN ALTERNATIVE FUEL USING CARBONIZATION AND BRIQUETING PROCESSES - Agustinus, Agustinus; Tambing, Enos; Mangalo, David; Joni, Joni; Pagasis, Thomas; Allo, Elisabet Payung (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The potential natural resources of Keerom Regency, Arso District, especially in the agricultural sector, are very abundant. Corn cob waste produced by farmers is a loss if it is not converted into something more useful. Corn cobs contain cellulose, hemicellulose, and lignin. This content will later be converted into smaller molecules through various treatments to be used as energy. This service aims to provide knowledge and skills to the farming community, on how to process corn cob waste as solid fuel or briquettes. The results of proximate testing or the composition of corn cob briquettes carried out in the Unhas Animal Husbandry Laboratory showed that at the highest temperature of 100oC, fixed carbon was obtained at 39.7, and at the lowest temperature of 60oC, fixed carbon was at 41.3. This can be stated as the amount of carbon contained in the remaining material after the volatile matter has been removed. Likewise, the higher the fixed carbon value, the quality of the corncob briquettes increases. Thus, the highest energy or heat pattern obtained is 5933 cal/gr, so corn cob briquettes can be used as briquette fuel energy. Utilizing corn cobs as fuel for briquettes can reduce dependence on fuel oil and can be used as a home industry business.